High-mobility flexible oxyselenide thin-film transistors prepared by a solution-assisted method - Congcong Zhang; Jinxiong Wu; Yuanwei Sun; Tan, Congwei; Tianran Li; Teng Tu; Yichi Zhang; Yan Liang; Xuehan Zhou; Peng Gao; Hailin Peng (J. Am. Chem. Soc., 2020)
Two-dimensional (2D) semiconductors hold great promise in flexible electronics because of their intrinsic flexibility and high electrical performance. However, the lack of facile synthetic and subsequent device fabrication approaches of high-mobility 2D semiconducting thin films still hinders their practical applications. Here, we developed a facile, rapid, and scalable solution-assisted method for the synthesis of a high-mobility semiconducting oxyselenide (Bi2O2Se) thin film by the selenization and decomposition of a precursor solution of Bi(NO3)3·5H2O. Simply by changing the rotation speed in spin-coating of the precursor solution, the thicknesses of Bi2O2Se thin films can be precisely controlled down to few atomic layers. The as-synthesized Bi2O2Se thin film exhibited a high Hall mobility of ∼74 cm2 V–1 s–1 at room temperature, which is much superior to other 2D thin-film semiconductors such as transition metal dichalcogenides. Remarkably, flexible top-gated Bi2O2Se transistors showed excellent electrical stability under repeated electrical measurements on flat and bent substrates. Furthermore, Bi2O2Se transistor devices on muscovite substrates can be readily transferred onto flexible polyvinyl chloride (PVC) substrates with the help of thermal release tape. The integration of a high-mobility thin-film semiconductor, excellent stability, and easy transfer onto flexible substrates make Bi2O2Se a competitive candidate for future flexible electronics.